Industry Leaders of open Distance learning Institutions Meet. - Borneo, Post (Borneo Post, 2018)
Asia e University (AeU) and commonwealth of learning (COL) co-hosted a two day International High Level Roundtable Conference for Open Distance Learning Institutions (ODL) at Holiday Villa Hotel and Conference Centre, Subang Jaya.